Reversal of cognitive deficits in FUSR521G amyotrophic lateral sclerosis mice by arimoclomol and a class I histone deacetylase inhibitor independent of heat shock protein induction - Pelaez, Mari Carmen; Fiore, Frédéric; Larochelle, Nancy; Dabbaghizadeh, Afrooz; Comaduran, Mario Fernández; Arbour, Danielle; Minotti, Sandra; Marcadet, Laetitia; Semaan, Martine; Robitaille, Richard; Nalbantoglu, Josephine N.; Sephton, Chantelle F.; et al. (Neurotherapeutics, 2024)
Protein misfolding and mislocalization are common to both familial and sporadic forms of amyotrophic lateral sclerosis (ALS). Maintaining proteostasis through induction of heat shock proteins (HSP) to increase chaperoning capacity is a rational therapeutic strategy in the treatment of ALS. However, the threshold for upregulating stress-inducible HSPs remains high in neurons, presenting a therapeutic obstacle. This study used mouse models expressing the ALS variants FUSR521G or SOD1G93A to follow up on previous work in cultured motor neurons showing varied effects of the HSP co-inducer, arimoclomol, and class I histone deacetylase (HDAC) inhibitors on HSP expression depending on the ALS variant being expressed. As in cultured neurons, neither expression of the transgene nor drug treatments induced expression of HSPs in cortex, spinal cord or muscle of FUSR521G mice, indicating suppression of the heat shock response. Nonetheless, arimoclomol, and RGFP963, restored performance on cognitive tests and improved cortical dendritic spine densities. In SOD1G93A mice, multiple HSPs were upregulated in hindlimb skeletal muscle, but not in lumbar spinal cord with the exception of HSPB1 associated with astrocytosis. Drug treatments improved contractile force but reduced the increase in HSPs in muscle rather than facilitating their expression. The data point to mechanisms other than amplification of the heat shock response underlying recovery of cognitive function in ALS-FUS mice by arimoclomol and class I HDAC inhibition and suggest potential benefits in counteracting cognitive impairment in ALS, frontotemporal dementia and related disorders.